Direct assay for endo-α-mannosidase substrate preference on correctly folded and misfolded model glycoproteins. (3rd November 2016) - Dedola, Simone; Izumi, Masayuki; Makimura, Yutaka; Seko, Akira; Kanamori, Akiko; Takeda, Yoichi; Ito, Yukishige; Kajihara, Yasuhiro
Abstract: We previously reported a unique assay system for UDP-glucose glycoprotein glucosyltransferase (UGGT) toward glycoprotein folding intermediates during the folding process. The assay involved the in vitro folding of both high-mannose type oligosaccharyl crambin, which yielded only the correctly folded glycoprotein form (M9-glycosyl-native-crambin), and its mutant, which yielded misfolded glycoproteins (M9-glycosyl-misfolded-crambin), in the presence of UGGT. The process successfully yielded both mono-glucosylated M9-glycosyl-native-crambin (G1M9-glycosyl-native-crambin) and M9-glycosyl-misfolded-crambin (G1M9-glycosyl-misfolded-crambin). Here, we report the use of our in vitro folding system to evaluate the substrate preference of Golgi endo-α-mannosidase against G1M9-native and -misfolded glycoprotein forms. In our assay Golgi endo-α-mannosidase removed Glc-α-1-3-Man unit from G1M9-native and -misfolded-crambins clearly proving that Golgi endo-α-mannosidase does not have specific preference for correctly folded or misfolded protein structure. Graphical abstract: Highlights: Endo-α-mannosidase is a Golgi enzyme, its role is not clear yet. It cleaves Glc-Man from A-arm of high-mannose oligosaccharide in N -glycoproteins. Folded and misfolded N -glycoprotein models were used to confirm its substrate specificity. Endo-α-mannosidase does not discriminate between correctly folded and misfolded glycoproteins.